Economic Growth and Female Participation in the Labour Market: Gender Disaggregated Data - Mose, Naftaly (Business and Economic Research, 2024)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The study aims to examine the impact of economic growth on female labour market participation in Kenya with data spanning between 1991 and 2022. Labour-force data disaggregated by gender are important to monitor the dynamic of gender inequalities in the labour market. The secondary data used to construct the time series was obtained from the World Bank and the International Labour Organization sources. The research was informed by the Feminisation U hypothesis, which describes the tendency of female labour force participation to first decline and then rise in the process of economic growth. The study used a fully modified ordinary least square (FMOLS) and Granger causality test to analyse the long-run effect of economic growth on women's participation in the labour market. The study results indicate that economic growth positively and significantly contributes to women’s participation in the labour market in the long run. Furthermore, the results of the control variables suggest that education has a beneficial effect on women's workforce, while women’s access to the workforce is hampered by male labour market participation, fertility rate, female self-employment and rate of urbanization. The study suggests to policymakers that the strategy to success is to facilitate education, vocational training, and social change that enable women to play the same role as men in the labour market. Finally, women must be in productive sectors and government should remove barriers to ownership of factors of production to encourage them to participate in economic activities and the labour market.